Effect of citalopram on hippocampal volume in first-episode schizophrenia: Structural MRI results from the DECIFER trial. (30th June 2021) - Qi, Wei; Blessing, Esther; Li, Chenxiang; Ardekani, Babak A; Hart, Kamber L; Marx, Julia; Freudenreich, Oliver; Cather, Corinne; Holt, Daphne; Bello, Iruma; Diminich, Erica D; Tang, Yingying; et al.
Highlights: Hippocampal atrophy is prominent in early psychosis and has been linked to negative symptoms. Add-on citalopram during the maintenance phase of treatment improved negative symptoms. Citalopram did not affect hippocampal volume over 6 months. Cortical thickness in 4 regions correlated with negative symptoms, unrelated to citalopram. Effects on brain volume did not account for citalopram's improvement of negative symptoms. Abstract: Hippocampal volume loss is prominent in first episode schizophrenia (FES) and has been associated with poor clinical outcomes and with BDNF genotype; antidepressants are believed to reverse hippocampal volume loss via release of BDNF. In a 12-month, placebo-controlled add-on trial of the antidepressant, citalopram, during the maintenance phase of FES, negative symptoms were improved with citalopram. We now report results of structural brain imaging at baseline and 6 months in 63 FES patients (34 in citalopram group) from the trial to assess whether protection against hippocampal volume loss contributed to improved negative symptoms with citalopram. Hippocampal volumetric integrity (HVI) did not change significantly in the citalopram or placebo group and did not differ between treatment groups, whereas citalopram was associated with greater volume loss of the right CA1 subfield. Change in cortical thickness was associated with SANS change in 4 regions (left rostral anterior cingulate, right frontal pole, right cuneus, and right transverse temporal) but none differed between treatment groups. Our findings suggest that minimal hippocampal volume loss occurs after stabilization on antipsychotic treatment and that citalopram's potential benefit for negative symptoms is unlikely to result from protection against hippocampal volume loss or cortical thinning.